Technical report: a study of heat transfer in double and triple window pane: a case study in Turkey / Nurallya Syuhada Abdul Malik - Abdul Malik, Nurallya Syuhada (2017)
In this study, the heat transfer through double and triple pane windows are numerically analyzed by using Fourier's Law of heat conduction. The aim of this study are to find heat transfer in double and triple windows by using different types of materials and different gap lengths between the windows in different outdoor temperature and to find the best types of materials used for windows and suitable gap lengths between the windows in different outdoor temperature. The temperature data comes from Ankara and Kars cities of Turkey. The result show that heat losses through the windows can be reduced by increasing the gap width between the windows by using polycarbonate sheet instead of glass.